Perfomance analysis of a small animal PET scanner using 68Ga Isotope - Victória Garcia Moreira; Anna Clara Moreira Silva; Rodrigo Modesto Gadelha Gontijo; Andréa Vidal Ferreira (Brazilian Journal of Radiation Sciences)
In recent years, the use of PET scanners for small animals in preclinical research has been growing in Brazil, due to this fact it is essential to have a quality assurance program to ensure the good performance of these scanners or indicate the need for corrective maintenance. In 2008, the National Association of Electrical Equipment Manufacturers (NEMA) in the USA published a document that proposes the following tests to ensure quality control: uniformity, spill-over ratio, and recovery coefficients. Thus, the objective of this work was to evaluate the image quality of the PET scanner for small animals LabPET SOLO 4 using the isotope Gallium-68. The results revealed that the use of the isotope 68Ga was quite different from standard tests using 18F. The project provided us with a comprehensive understanding of the functioning of the PET scanner when employing the radionuclide 68Ga. This evaluation is of crucial relevance for application in laboratories, especially in the quantitative analysis of PET images and in the planning of preclinical studies